Brazilian International Students’ Satisfaction with Migration Life in Portugal - Neto, Félix (Journal of International Students, 2022)
International students constitute an important sojourner group. The current research aimed to test the psychometric characteristics of the Satisfaction with Migration Life Scale (SWMLS) for international students, and the role of different psycho-social variables in predicting SWMLS. The sample included 189 Brazilian college students who attended Portuguese institutions of higher education. Sixty-three percent were females and 37% males, aged between 18 and 38 years. The average length of sojourn in Portugal was 14 months. The confirmatory factor analysis revealed that the one-dimensional model of the SWMLS is adequate and possesses good internal consistency. The study found that international students are generally satisfied about their migration life. Subsequent analysis indicated that the SWMLS scores were significantly associated with other measures of financial status, perceived discrimination, cultural intelligence, sociocultural adaptation, and subjective well-being. Suggestions for future research with international students are proposed.